Indicadores de resiliência para gestão de contingências em uma empresa de transporte aéreo regular - Rad, Eduardo Alberto Casagrande (2017)
One of the major organizational challenges for airlines is to maintain the continuity of their operations, copying with problems involving airport closures, infrastructure issues and unscheduled maintenance events. To deal with these contingencies, companies use Control Centers of Operations (CCOs), whose responsibility involves planning and monitoring the execution of planning their flight schedules while attempting to accommodate the variability encountered. This type of activity creates the need for the system to be resilient, that is, the ability to adapt system operation before, during or after some change or disorder in order to maintain expected operations, under expected and unexpected contexts. The objective of this study is to propose indicators of resilience that aim to help manage the main contingencies experienced by the CCO, increasing the operational capacity of the planned operations, even in the face of unexpected situations. This research presents a single case study of a regular air transport company that operates around 800 daily flights throughout Brazil and in some international destinations. A systemic mapping of the main contingencies experienced by CCO were performed using the Functional Resonance Analysis Method (FRAM). Data was gathered by means of interviews, in locus observations and analysis of technical documents. Two indicators of resilience have been proposed that have the potential to indicate where and when the system defenses should concentrate their efforts in order to avoid contingencies. The use of FRAM and the principles of Resilience Engineering (ER) have shown promise for the identification of resilience indicators, and the proposed method may be used in future research that seeks to identify indicators of resilience in complex sociotechnical systems.